Effect of Diets with the Addition of Edible Insects on the Development of Atherosclerotic Lesions in ApoE/LDLR-/- Mice - Hassen, Hayat; Škvorová, Petra; Pokhrel, Kshitiz; Kulma, Martin; Piątkowska, Ewa; Kostogrys, Renata B; Kouřimská, Lenka; Tarko, Tomasz; Franczyk-Żarów, Magdalena (International journal of molecular sciences, 2024)
Foods enriched with insects can potentially prevent several health disorders, including cardiovascular diseases, by reducing inflammation and improving antioxidant status. In this study, Tenebrio molitor and Gryllus assimilis were selected to determine the effect on the development of atherosclerosis in ApoE/LDLR-/- mice. Animals were fed AIN-93G-based diets (control) with 10% Tenebrio molitor (TM) and 10% Gryllus assimilis (GA) for 8 weeks. The nutritional value as well as antioxidant activity of selected insects were determined. The lipid profile, liver enzyme activity, and the fatty acid composition of liver and adipose tissue of model mice were evaluated. Quantitative analysis of atherosclerotic lesions in the entire aorta was performed using the en face method, and for aortic roots, the cross-section method was used. The antioxidant status of the GA cricket was significantly higher compared to the TM larvae. The results showed that the area of atherosclerosis (en face method) was not significantly different between groups. Dietary GA reduced plaque formation in the aortic root; additionally, significant differences were observed in sections at 200 and 300 µm compared to other groups. Furthermore, liver enzyme ALT activity was lower in insect-fed groups compared to the control group. The finding suggests that a diet containing edible insect GA potentially prevents atherosclerotic plaque development in the aortic root, due to its high antioxidant activity.
Keywords: játra; aorta; Tenebrio; atherosclerosis; LDL-receptory; Animal Feed; Diet; jedlý hmyz; mouse model; Edible Insects; liver enzymes activity; ateroskleróza; Antioxidants; zvířata; Tenebrio molitor; myši; antioxidant status; lipid profile; aterosklerotický plát; Mice; myši knockoutované; Gryllidae; antioxidancia; Liver; Receptors, LDL; Male; krmivo pro zvířata; Atherosclerosis; Mice, Knockout; Gryllus assimilis; dieta; Apolipoproteins E; fatty acids profile; Animals; mužské pohlaví; Aorta; Plaque, Atherosclerotic; Disease Models, Animal; apolipoproteiny E; modely nemocí na zvířatech